The Home Environments of Infants of Mothers with Early, Remitted Clinical Depression and No Depression during the First Two Years Postpartum - Lauren M. Henry; Nanmathi Manian; Gianluca Esposito; Marc H. Bornstein (MDPI AG, 2023)
The current study examines stability, continuity, and group and gender differences in the home environments of infants of mothers with early, remitted clinical depression and no postpartum depression, overcoming methodological variations in the extant literature. Fifty-five mothers diagnosed with clinical depression (major or minor depression, dysthymia, or depressive disorder not otherwise specified) at 5 months and fully remitted by 15 and 24 months, and 132 mothers with no postpartum depression (Mage = 32.47; 69.7% European American) completed the Home Observation for Measurement of the Environment (HOME) Inventory Infant/Toddler version when their infants were 15 and 24 months old. No differences in stability estimates of the HOME scales were found between the groups. In terms of continuity, controlling for maternal education and infant birth order, HOME responsivity, involvement, and total score decreased, while HOME acceptance increased between 15 and 24 months in the full sample. There were no effects of group or gender. Results may point to the home environment as a key protective factor for infants of mothers with early, remitted clinical depression, or findings may suggest improved maternal parenting cognitions and practices following remission.